HUMAN CAPITAL’S IMPORTANCE IN ICOS SUCCESS - Campino, J.; Brochado, A.; Rosa, A. (CORPORATE GOVERNANCE: EXAMINING KEY CHALLENGES AND PERSPECTIVES, 2020)
Initial coin offerings (ICOs) are an alternative investment form offering the possibility of direct financing from worldwide investors and contribute to the democratization of entrepreneurship and access to capital markets. The ICOs are based on the blockchain technology and offer the chance to invest in a project’s initial phase through the acquisition of a token (Brochado, 2018). It also allows tokens’ transaction on the secondary market which is essential to their success (Chen, 2018). There are three main types of token which vary according to their purpose and investors’ rights: 1) currency token: used as a means of exchange and store such as a cryptocurrency; 2) security token: used as conventional security but recorded and exchanged on a blockchain; the underlying of this token type can range from corporate equity (typical share) to commodities, real estate or even currencies; 3) utility token: is the most common token type and provides to the buyer consumptive rights to access a product or service (Howell, Niessner, & Yermack, 2018). Since the first ICO of MasterCoin in 2013 proposed by J. R. Willett the interest on this topic has been increasing and reached a peak between the years of 2017-2018. This is confirmed by an analysis of Google trends for the word “ICO” at a worldwide level (Google, 2020). This increase in popularity goes hand in hand with the appreciation of cryptocurrencies during the same period. Indeed, the market capitalization of cryptocurrencies influences the amounts raised by ICOs (Masiak, Block, Masiak, Neuenkirch, & Pielen, 2018; OECD, 2019; Fisch, 2019). The literature has been following this tendency and several studies have focused on ICOs although there are still several literature gaps due to the novelty, different and complex interaction of an ICO process. The studies’ focus has also been on the success factors of ICOs (An, Duan, Hou, & Xu, 2019; Fisch, 2019; Goergen & Rondi, 2019;Giudici & Adhami, 2019; OECD, 2019). The current paper intends to focus particularly on human capital which is considered to be an essential factor in a successful venture (An et al., 2019). The common measure for asserting an ICO’s success has been the amount raised in the campaign (Fisch, 2019). ICOs propose to achieve both soft-cap (least amount the funders will accept to proceed with the project) and hard-cap (maximum amount the founders will accept) thresholds. Therefore, the time elapsed until achieving one of these limits is also a measure of ICOs’ success along with the amount raised (An et al., 2019). In terms of human capital, the characteristics of the founding team can be considered the following: 1) experience in the financial sector; 2) experience in computer science; 3) experience in blockchain projects; 4) entrepreneur’s profile; 5) number of founders; 6) existence of social media accounts (Brochado, 2018). In the current study, the authors propose to analyze human capital as an ICO’s success factor using a database collected from ICObench1 via its API through computer programing. The database was filtered in order to comprise 556 ICOs in the banking/financial sector. The database also included information on the founders’ profile who the current paper will study. It was possible to complement the information on the database with public information available on the LinkedIn profiles. The result was extra information of 4552 founders’ profiles.